Multiple Meanings: The Role of Black Gospel in an Interracial and Multi-Ethnic Edmonton Church - Taranger, Angela (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1999)
This paper examines the process by which Black gospel music (performed according to aesthetic standards determined by African Americans) has become a site of meaning for both Black and White congregants at Edmonton Community Worship Hour, a church with an interracial and multi-ethnic ministry. Certain "transformations" (or "inversions") are at play in the conceptual systems of the people who attend; each individual has disparate, though intersecting, webs of meaning which become operational in a cross-cultural setting, relating to: the music itself, the method of worship, and the interpersonal relationships of the church's Black majority and White minority.